2008
DOI: 10.1016/j.neulet.2007.11.068
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK as a negative regulator of VEGF/VEGFR2 signaling pathway in serum deprived human SK-N-SH neuroblastoma cells

Abstract: Evidence suggests that vascular endothelial growth factor (VEGF) mediates neuroprotection to prevent an apoptotic cell death. The p38 mitogen activated protein kinase (MAPK) pathway is implicated as an important mediator of neuronal apoptosis but its role in VEGF-mediated neuroprotection is unclear. Herein, we show that treatments with the p38 MAPK inhibitor, SB202190, enhanced VEGF-mediated survival in serum deprived SK-N-SH neuroblastoma cells by decreasing caspase-3/7 activation while increasing the phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…Additional phosphorylation of p38MAPK, which is involved in actin reorganization, was decreased in forebrains of Flt-1TK Ϫ/Ϫ mice. This is in conformity with current studies reporting that p38MAPK signaling is opposing VEGFR-2-mediated effects of VEGF-A on neuroblastoma and endothelial cells (Yilmaz et al, 2003;Gomes and Rockwell, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additional phosphorylation of p38MAPK, which is involved in actin reorganization, was decreased in forebrains of Flt-1TK Ϫ/Ϫ mice. This is in conformity with current studies reporting that p38MAPK signaling is opposing VEGFR-2-mediated effects of VEGF-A on neuroblastoma and endothelial cells (Yilmaz et al, 2003;Gomes and Rockwell, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…It is noteworthy that, in brain lysates of Flt-1TK Ϫ/Ϫ mice, the enhanced VEGFR-2 phosphorylation was accompanied by a vast decline in phosphorylation of p38MAPK, which has been shown to oppose VEGF-A signaling in neuroblastoma (Gomes and Rockwell, 2008) and human umbilical vein endothelial cells (Yilmaz et al, 2003). Concurrently, slightly increased phosphorylation of Paxillin, a component of the focal adhesion that is known to play a regulatory role in VEGF-induced endothelial cell migration (Kanno et al, 2000), was detected in brain lysates (Fig.…”
Section: Vegfr-1 Deletion and Increased Vegf-a Protein Levels Increasmentioning
confidence: 99%
“…P38MAPK is a molecular switch between VEGF induced angiogenesis and vascular hyperpermeability; it negatively regulates angiogenesis by reducing phosphorylation of Erk1/2 and increases permeability by yet unidentified mechanisms. Inhibition of P38MAPK enhances survival, plasminogen activation, and Erk-1/2 phosphorylation [26,41]. Here, we showed that deltonin could inhibit AKT and ERK1/2 phosphorylation but increase the phosphorylation of P38MAPK, which indicated the negative effect of P38MAPK on ERK1/2 and VEGF induced angiogenesis, consistent with the previous research.…”
Section: Discussionsupporting
confidence: 91%
“…ERK1/2 can be stimulated by extracellular growth factor then regulate many substrates, such as nuclear factor-jB and cJun; they play a critical role in regulating endothelial cell cycle, proliferation, migration, apoptosis and angiogenesis [21,23]. P38MAPK could be activated in response to environmental stress and inflammatory cytokines [24,25], the phosphorylation of P38MAPK could affect the migration and apoptotic of endothelial cells, it also could decrease VEGF-induced angiogenesis [26,27]. All of these pivotal pathways collaboratively promote proliferation, migration, invasion and differentiation to capillary-like structure of endothelial cells in the preexisting vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Gratton et al reported that p38 depresses Akt levels resulting in apoptotic signaling (Gratton et al, 2001). Similarly, serum starvation induced apoptosis in neuronal cells that was mediated by p38 (Gomes and Rockwell, 2008). However, p38α deletion results in homozygous embryonic lethality due to reduced vascularization and increased apoptosis (Mudgett et al, 2000), suggesting that p38 provides a positive stimulus to sustain the vasculature.…”
Section: Introductionmentioning
confidence: 99%